INNOVATIVENESS OF DIDACTIC PRACTICE IN THE FIELD OF CURRENT PEDAGOGICAL KNOWLEDGE - Prauzner, Tomasz (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The theory of education, which is didactics, in the realities of today's educational practice and upbringing is becoming more important in the work of a teacher. The theory of education is improving thanks to newer empirical knowledge created on innovative practice. Currently, there is a traditional division of education theory into general, specific, environmental and special didactics. However, in terms of new teaching aids and brain research methods, it is worth considering its new meaning.